2022
DOI: 10.4082/kjfm.22.0099
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Physical Activity in South Korea

Abstract: The health benefits of physical activity have been well established. However, more than a quarter of the adult population in the world is insufficiently active (not performing at least 150 minutes of moderate-intensity physical activity per week, 75 minutes of vigorous-intensity physical activity per week, or any equivalent combination of the two), and there has been little improvement since 2001. In South Korea, the prevalence of insufficient physical activity was 54.4% in adults and 94.1% in adolescents in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…This suggests our participants are active overall and are less limited by arterial stiffness or anxiety symptoms, which may partially explain why there was no significant association between arterial stiffness and anxiety symptoms [ 45 ]. Furthermore, our study participants showed a higher level of physical activity level than that of the average Korean population (50.30% vs. 45.6%) [ 49 ]. As physical activity levels are associated with decreased anxiety symptoms, this might have mitigated the potential relationship [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests our participants are active overall and are less limited by arterial stiffness or anxiety symptoms, which may partially explain why there was no significant association between arterial stiffness and anxiety symptoms [ 45 ]. Furthermore, our study participants showed a higher level of physical activity level than that of the average Korean population (50.30% vs. 45.6%) [ 49 ]. As physical activity levels are associated with decreased anxiety symptoms, this might have mitigated the potential relationship [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of Korean adults in 2020, 49.6% of the participants responded that their physical activity decreased after the COVID-19 pandemic, whereas only 5.7% said their level of physical activity increased [20]. A similar study reported that 54% of adults and 94.1% of adolescents did not meet the guidelines for physical activity [21]. This shows not only a lower level of participation in physical activity compared to the rest of the world but also a worse indicator than in the past.…”
Section: Introductionmentioning
confidence: 98%
“…A study has reported that the status of physical activity showed a wide distribution according to country, race, gender, and age. In addition to biological factors such as gender and age, psychological and social factors were found to be strongly related to physical activity [21]. Owing to the impact of the COVID-19 pandemic, people are faced with situations they have never experienced before, including restrictions on individual physical movement, psychological changes, and reduced social interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, exercise is difficult to sustain because health and environmental factors often act as barriers [ 12 ]. Only about 40% of Korean adults practice regular walking, and fewer than 24.7% of adults perform resistance exercise at least 2 days per week [ 13 ]. Therefore, new strategies to prevent muscle strength decline are needed.…”
Section: Introductionmentioning
confidence: 99%